Lung adenocarcinoma with repetitive endotracheal/endobronchial metastasis 20 years after surgery: A case report. Issue 1 (14th November 2020) - Maki, Yohei; Kimizuka, Yoshifumi; Sasaki, Hisashi; Yamamoto, Takayuki; Watanabe, Chie; Sano, Tomoya; Tagami, Yoichi; Misawa, Kazuhisa; Miyata, Jun; Fujikura, Yuji; Shimazaki, Hideyuki; Kawana, Akihiko
Abstract : The occurrence of endotracheal/endobronchial metastasis (EEM) after complete resection of a primary lung cancer is rare. Here, we report the case of an 86‐year‐old woman in whom EEM occurred twice over a 20‐year period following complete resection of a primary adenocarcinoma localized to the left main bronchus and trachea. The presence of EEM was confirmed by establishing immunohistochemical homology of the metastases with the primary tumor. To the best of our knowledge, this is the first reported case of repetitive EEM of primary lung adenocarcinoma. Lymphatic invasion in the primary lesion suggested that a possible route for EEM was the peripheral lymphatic tract, explaining the slow recurrence rate. We conclude that observation of the trachea/bronchus over a long period post operation could be important in monitoring for EEM, particularly if lymphatic invasion is confirmed in the primary tumor. Abstract : This is the first reported case of repetitive localized endotracheal/endobronchial metastasis of primary lung adenocarcinoma with mild lymphatic invasion that occurred twice over a 20‐year period after complete resection. Observation of the trachea/bronchus over a long period post operation could be important in monitoring for endotracheal/endobronchial metastasis, particularly if lymphatic invasion is confirmed in the primary tumor.